Disinflationary Spillovers from The Euro Area into the Countries of Southeastern Europe - Gani Ramadani; Predrag Pandiloski (Journal of Central Banking Theory and Practice, 2019)
We analyse the determinants of the inflation trends in ten Southeast European (SEE) countries. Global cost-related factors and euro area inflation developments play an important role in explaining inflation dynamics in SEE countries. Changes in world food and energy prices, together with related changes in administered prices, similarly contribute to these trends. In general, we show that disinflationary spillovers from the euro area have been an important factor for fixed exchange rate regime countries, especially those with more trade exchange with countries in the euro area. Furthermore, our heterogeneity analysis shows that countries with less rigid exchange rate regimes but with relatively high exposure of trade exchange to the euro area (EA) market appear to be susceptible to inflation spillovers from the euro area. Moreover, nominal effective exchange rate plays an important role in inflation process in SEE countries, particularly in floating regime countries. In line with several recent findings about flattening of the Phillips curve in many economies across the world, cyclical unemployment does not appear to be significant in our sample. We conclude with some policy implications of our results.
Keywords: C33; E12; E31; 330; inflation; Phillips curve; panel data; euro area inflation; commodity prices; Southeast European countries